Micro Hybrid Power Generation Using Solar and Wave Energy - Mohamad Nasri, Mohamad Shafiq; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2023)
When we talk about renewable energy, what pops into your mind? Of course, you will think about unlimited resources of supply through nature. Recently there were many cases of nature disaster due to the pollution that were caused by mankind. In order to overcome this problem, my first small step for this huge change is to create a device that can harness the energy of renewable energy from wave and solar energy. For the wave energy, where else the method to harness the wave energy is by applying the full wave rectifier circuit to make the stepper motor generate the energy with the rotation of the shaft motor. The wave energy that produces kinetic energy will cause the buoy to float up and down. Hence, the buoy is implemented with the gear slider. This action will make the gear slider to slide the shaft motor, so that it will generate the energy by using wave kinetic motion. But since the value generated was too small, the circuit will only be used to light up a bright LED to show it generates voltage. For solar panel was placed on top of the water container to harness the solar energy. For the safety of the process a circuit was constructed suitable with the component used in the device. From the wave and solar energy, it will be combined into one device. So, it will make a micro hybrid power generation using waves and solar energy.